STATUS MUTU AIR DAN STRATEGI PENGENDALIAN PENCEMARAN SUNGAI KANIBUNGAN PULAU SEBUKU KABUPATEN KOTABARU - Murjani, Akhmad; Fatmawati; Siswanto (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
The quality of the river will undergo changes in accordance with the development of the river environment which is influenced by various activities and human life. This study aims to analyze the status of water quality in the Kanibungan River based on a comparison of quality standards and water quality index with the pollution index method and river water pollution control strategies. Measurement of research parameters at three locations, namely the upstream, middle, and downstream of the Kanibungan River. Insitu sampling and laboratory tests. Water quality parameters are TSS, pH, BOD5, DO, Mn, H2S, Fat and Oil. Quality standards based on South Kalimantan Governor Regulation No. 5 of 2007 class I water quality classification and KAN accredited Parameters (ISO/IEC 17025). The pollution index is based on the Decree of the Minister of Environment No.115 of 2003. The results of the research on water quality compared to class I water quality standards for parameters, TSS, pH, dissolved oxygen, Fe, Mn, H2S and oils and fats meet the quality standards, water quality BOD5 exceeds the quality standard. The water quality status of the upstream, middle and downstream of the river is included in the slightly polluted category with a value range of 2.5213-2.5507. River pollution control strategies can be carried out by reducing pollution loads, namely by community-based river environmental management, involving supervision from the local government.